Diagnóstico dos crimes ambientais e ações de prevenção na área de atuação do 2º Batalhão Ambiental da Brigada Militar - Guimarães, Luis Garcia (2009)
Today, when information plays a role ever more relevant, there is much discussion about the environmental crisis and the urgent need for a change in the human attitude towards our environment, and hence, ourselves. A part of humankind is becoming aware of the necessity to preserve the natural environment, in order to stop the destruction of its own species. Therefore, in this dissertation, we sought to identify, locate and evaluate, within a timescale, the Environmental Crime Fighting Activities and the Environmental Crime Preventive Activities performed by the contingent of 2º Environmental Battalion of Brigada Militar (2º EBBM). The research was done through data gathering at the eleven areas which make the environmental subdivisions of the 2º EBBM, referring to years from 2006 up to 2008. These data present themselves as incidents attended by the contingents of both the Environmental Groups (EG) and Platoons, on the matters of flora, fauna, pollution, mining, other environmental incidents, weapon capture, fishing net capture, capture of other materials, fabricated documents, flagrant arrests and Particular Terms; and also the data on the Environmental Education activities. Thereby, as the research took place, we concluded that the activities of contaminating streams, polluting the atmosphere, devastating forests, indiscriminate hunting and fauna habitat reduction, or even ravaging, plus many other means of environmental aggression, are still common. Finally, we could perceive that Informal Environmental Education plays an important role in preventing Environmental Crime, allowing a change of behavior by the society as part of the struggle for a healthy Environment.